> 数学 >
初一下数学题 那位好心人帮帮忙
(1)(2x+y+1)(2x+y-1)(2)(x-2)(x+2)-(x+1)(x-3) (3)(ab+1)²-(ab-1)²
(4)(2x-y)²-4(x-y)(x+2y)
利用完全平方公式计算
(1)63²(2)998²
人气:204 ℃ 时间:2020-01-26 14:06:45
解答
1(2x+y+1)(2x+y-1)
= (2x+y)^2-1^2
=4x^2+y^2+4xy-1
(2)(x-2)(x+2)-(x+1)(x-3)
=(x^2-2^2)-(x^2-3x+x-3)
=x^2-4-x^2+2x+3
(3)(ab+1)²-(ab-1)²
=a^4 b^4-1
(4) (2x-y)²-4(x-y)(x+2y)
=(4X^2+y^2-4xy)-(4x^2+4xy-y^2)
=2y^2-8xy
利用完全平方公式计算
(1)63²
=(60+3)^2
=60^2+3^2+2*60*3
=3600+9++360
=3969
(2)998²
=(1000-2)^2
=1000²-2*1000*2+2²
=1000000-4000+4
=996004
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版